Surfactants in Upstream E&P - Solling, Theis; Shahzad Kamal, Muhammad; Shakil Hussain, Syed M. (Petroleum Engineering, Sustainable Geoenergy Engineering and Technology, 2021)
VIII, 468 p. 215 illus., 137 illus. in color.